Assessment of the dynamics of autophagy and apoptosis biomarkers in the acute period of ischemic stroke using flow cytometry - A. V. Lugovaya; Yu. V. Emanuel; A. V. Artemova; E. V. Semenova; V. V. Semenova (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
The objective was to conduct a comparative analysis of the dynamics of biomarkers of apoptosis and autophagy in the eripheral blood of patients in the acute period of ischemic stroke (IS) and compare it with the dynamics of the severity of neurological deficit according to the NIHSS (National Institutes of Health Stroke Scale) and the volume of the brain lesion according to the results of magnetic resonance imaging (MRI). To assess the role of the studied parameters in the prognosis of the outcome of the acute period of the disease.Methods and material. We examined 56 patients in the acute period of newly developed atherothrombotic IS. The control group consisted of 29 healthy donors. Patients underwent a dynamic clinical and neurological examination on the 1st, 7th and 14th days from the onset of the disease. At the same time intervals, the dynamics of the expression of biomarkers of apoptosis and autophagy in peripheral blood was evaluated by flow cytometry and compared with neurological status indicators on the 1st, 7th, and 14th  days, respectively, using correlation analysis.Results. A statistically significant increase in the expression of annexin V and caspase-3 compared with the control group was observed throughout the study in all populations of leukocytes with a maximum increase in the first 24 hours. Increased expression levels of annexin V and caspase-3 positively correlated with the severity of neurological deficit and the amount of brain damage on the 1st and 7th days. A direct correlation was found between increased values of autophagy biomarkers LC3, Cyto-ID, the amount of brain damage, and the severity of neurological deficit on the 7th day.Conclusion. A statistically significant increase in biomarkers of apoptosis and autophagy in the peripheral blood in the acute period of IS correlates with the severity of clinical and neurological parameters. The role of a significant increase in caspase-3 as a predictor of adverse disease outcome requires further study.